Indices de vegetação na mensuração do estoque de carbono em áreas com cana-de-açúcar - Polonio, Vanessa Durante [UNESP] (2015)
The cultivation of sugarcane has great environmental influence in Brazil, because sugarcane manual harvesting has been replaced by mechanized harvesting in São Paulo and this has caused a major drop in greenhouse gas emissions. Since 2007 the agreement was signed in the Environmental Protocol of the sugarcane industry. Thus, recent studies highlight the possibility of using spectral vegetation indices to estimate the biomass, the stock and carbon sequestration in monitoring the sugarcane crop. Through technological advances of remote sensors that allow to analyze, through satellite image, the spatial distribution of cultivated areas and possible changes in vegetation cover at different times, enable the monitoring of vegetated areas. As well as the main study hypothesis was that vegetation indices can discriminate different areas with different carbon stocks in areas cultivated with sugarcane, for the municipality of São Manuel - SP. The study area is located in the municipality of São Manuel - SP, were used to validate two areas of sugarcane in Botucatu - SP for comparison analysis. The processing and evaluation of data, generation of vegetation indices were prepared by ArcGIS 10.2.2 programs using satellite Landsat 8 bands. Were prepared correlation between vegetation indices in the validation of areas where there was a high correlation, it was possible to confirm the figures for the municipality of São Manuel - SP and interpret them with the assurance of spectral responses. Through the carbon inventory values in the soil in these areas in Botucatu - SP was performed with the correlation values of vegetation indexes generated in this case there was no correlation. One explanation for the low correlation between indexes related to biomass and carbon content in the soil is that the areas are cultivated with semi-perennial crop, which systematic soil disturbance beyond the demand management ...